2,2'-Diethoxy-4,4'-(E, E)-hydrazinediyl- idenebis(methanylylidene)diphenol - Al-Mehana, W.N.A.; Yahya, Rosiyah; Sonsudin, F.; Al-Mehana, I.N.A.; Lo, K.M. (International Union of Crystallography, 2012)
The complete molecule of the title compound, C 18H 20N 2O 4, is generated by inversion symmetry. The conformation around the C=N bond is E. With the exception of the ethoxy substituent, the molecule is essentially planar with an r.m.s. deviation of 0.0455 Ã. In the crystal, molecules are linked by O - HÂ·Â· Â·N hydrogen bonds into a two-dimensional supra-molecular network parallel to the bc plane.